Isotopic Characteristics and Water Interaction of Ifni Lake and Spring of Tifnoute Valley (High Atlas Mountains, Morocco, North of Africa) - Kacem Lamyaa; Agoussine M’bark; Igmoullan Brahim; Amar Hicham; Mokhtari Soraya; Ait Brahim Yassine (European Scientific Journal, ESJ, 2018)
Geochemical and isotopic investigations were carried out to indicate the interaction process between Ifni Lake water and high valley of Tifnoute springs. A total of 18 water samples were collected and analyzed. The Ifni Lake constitutes a veritable water resource in the study area, and this water can be the origin of alimentation the springs located in the high valley the Tifnoute. This study aims to improve the interaction between Ifni Lake water and the springs of high valley of Tifnoute. It is mainly focused to identify the origin of groundwater recharge and mineralization. The environmental isotope (deuterium (δ2H) and oxygen-18 (δ18O)) measurements allowed understanding the hydro geochemical process, the origin of the mineralization of the water. Also the results identify the relationship between the waters of Ifni Lake and the spring's water of high valley of Tifnoute. The isotopic compositions reveal that the origin of Ifni Lake water is meteoric, and the water infiltrates directly in the groundwater without any evaporation.